2016
DOI: 10.1039/c5cp07762a
|View full text |Cite
|
Sign up to set email alerts
|

Facile preparation of β-/γ-MgH2 nanocomposites under mild conditions and pathways to rapid dehydrogenation

Abstract: , which is ca. 46 % lower than that of commercial MgH2. Analysis suggests that the meta-stable γ-MgH2 component either directly dehydrogenates exothermically or first transforms into stable β-MgH2 very close to the dehydrogenation onset. The improved hydrogen release performance can be attributed both to the existence of the MgH2 nanostructure and to the presence of γ-MgH2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 36 publications
0
27
0
Order By: Relevance
“…Taking advantage of MgH2 NPs with a relatively high surface energy as heterogeneous sites, which exhibits favorable adsorption of tetrahydrofuran (THF) containing LiBH4 [25] , and the hydrophobic nature of graphene, which is incompatible with THF [26,27] [ 31,32] Interestingly, the enthalpy changes of dehydrogenation of 2LiBH4-MgH2 nanocomposite are calculated to be ~46.8 kJ mol -1 H2, which is significantly lower than the relative value of the bulk counterpart attributed to the favorable formation of In the light of these observations, the superior hydrogen storage performance and cycling stability of graphene-supported 2LiBH4-MgH2 nanocomposite can be mainly ascribed to several unique features. First, the high surface area of graphene and the unique self-assembly strategy make it possible to realize the high loading of uniform MgH2 NPs and hence LiBH4 NPs, which ensures the high capacity of the system (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Taking advantage of MgH2 NPs with a relatively high surface energy as heterogeneous sites, which exhibits favorable adsorption of tetrahydrofuran (THF) containing LiBH4 [25] , and the hydrophobic nature of graphene, which is incompatible with THF [26,27] [ 31,32] Interestingly, the enthalpy changes of dehydrogenation of 2LiBH4-MgH2 nanocomposite are calculated to be ~46.8 kJ mol -1 H2, which is significantly lower than the relative value of the bulk counterpart attributed to the favorable formation of In the light of these observations, the superior hydrogen storage performance and cycling stability of graphene-supported 2LiBH4-MgH2 nanocomposite can be mainly ascribed to several unique features. First, the high surface area of graphene and the unique self-assembly strategy make it possible to realize the high loading of uniform MgH2 NPs and hence LiBH4 NPs, which ensures the high capacity of the system (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…91 Apart from doping MgH 2 powders with catalysts, it has been experimentally demonstrated by some authors that changing the crystal structure of the stable b-tetragonal MgH 2 phase to a less stable phase of g-orthorhombic MgH 2 leads to improved gas uptake/ release kinetics and a decrease in the hydrogenation temperature without a drastic decrease in the storage capacity. [91][92][93] b-to-g phase transformations can be attained via severe plastic deformation (SPD) 94 at ambient temperature using different approaches such as HEBM, 95 cold rolling, 96 equal channel angular pressing (ECAP), 97 and high pressure torsion (HPT). 98 Commonly the results of these employed techniques demonstrated that formation of a nanocrystalline phase along with introducing high intensity defects, leads to an increase of the density of the grain boundaries.…”
Section: Development Of High Performance Pure Mgh 2 By Severe Plasticmentioning
confidence: 99%
“…proposed that a high density of defects may form in the Mg lattice through the adapted Rieked method. In addition,Xiao et al (2016) synthesized β-/γ-MgH 2 nanocomposites via a simple wet chemical route by ball milling MgH 2 with LiCl as an additive at room temperature followed by THF treatment and revealed that THF solution plays a vital role in the synthesis of the γ-MgH 2 phase. In this work, high-density defects formed in the nanocomposite and THF solution effect may contribute to the formation of the γ-MgH 2 phase at lower temperature.…”
mentioning
confidence: 99%